Pengaruh Daya Simpan Biopestisida Berbahan Aktif Virus SlNPV yang Diformulasikan Dengan Anti UV untuk Mengendalikan Ulat Grayak (Spodoptera litura F.) - Aqyla Rusnatha Putri (Fakultas Pertanian, 2025)
(Spodoptera litura F.) is one of the most significant pests affecting various crops in Indonesia, causing losses for farmers. Farmers still frequently control army worm pests using synthetic pesticides that have negative impacts on the surrounding environment. Entomopathogenic virus SINPV (Spodoptera litura Nuclear Polyhedrosis Virus) provides a more environmentally friendly control solution. However, there are constraints in using SlNPV, namely its inability to withstand sunlight exposure. Therefore, proper storage is necessary. This research used 2 factors: storage type and storage duration. Mortality test results from storage test samples showed that the experimental results did not show significant differences compared to the control treatment (storage on open desk at room temperature) with mortality rates above 50%. This indicates that there was no interaction between storage type and storage duration on S.litura mortality. ANOVA analysis results showed no interaction between storage type treatment and storage duration (ANOVA, sig 0.727), storage type treatment did not significantly affect SlNPV biopesticide effectiveness (ANOVA, sig 0.378), and storage duration treatment did not significantly affect the effectiveness of anti-UV protection-based SlNPV biopesticide (ANOVA, sig 0.585).
Entry oleh Arif 2026 Maret 26
Keywords: Army Worm; SlNPV; Storage